2012
DOI: 10.1017/jmech.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Initial Soil Suction with Compaction Conditions for Clayey Soils

Abstract: In this study, the initial soil suction of as-compacted clayey soils was evaluated for various compaction conditions, covering a wide range of compaction energy and molding water content. The soil specimens were prepared by impact compaction under three levels of compaction energy. The filter paper method was used to measure the initial soil suction of as-compacted specimens. Test results indicate that the relationship between the soil suction and the molding water content is bilinear under three different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…1 SWCC for the studied soil [19] Initial matric suction of soil samples prepared with 20% and 25% water content and degrees of compaction of 80%, 83%, and 86% were around 20kPa and 15kPa, respectively. This is consistent with the findings of Yang et al [24], who found that compaction energy has a lower impact on soil suction in soils having a lower clay content. The soil-water characteristic curve (SWCC) represents the relationship between matric suction and water content.…”
Section: Sample Preparationsupporting
confidence: 93%
“…1 SWCC for the studied soil [19] Initial matric suction of soil samples prepared with 20% and 25% water content and degrees of compaction of 80%, 83%, and 86% were around 20kPa and 15kPa, respectively. This is consistent with the findings of Yang et al [24], who found that compaction energy has a lower impact on soil suction in soils having a lower clay content. The soil-water characteristic curve (SWCC) represents the relationship between matric suction and water content.…”
Section: Sample Preparationsupporting
confidence: 93%
“…Yang et al [5] concluded that the resilient modulus of compacted subgrade soils is dependent on soil suction. The influence of compaction effort on soil suction has also been widely discussed [6][7][8]. Chu and Mou [6] found that matric suction of compacted soils with the same water content increases as compaction effort increases.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the total suction and matric suction are higher for clayey soils compacted with low energy than with high compaction energy. Yang et al [8] proposed reasonable models to explain these two kinds of suction behaviors of compacted soils.…”
Section: Introductionmentioning
confidence: 99%